Seismic capacity of building with soft storey - Kuah, Hong Sing. (2009)
This report serves to provide a summary of the theoretical knowledge and analytical skills gathered during the 2-semesters final year project (FYP) in NTU. As the author's topic of project focused mainly on seismic effects and building provisions, the study is a step up in relation to his field of study in civil engineering. It offered the author a chance to venture into a more specialized field of study. Therefore, it is a privilege to gain invaluable experience and knowledge about earthquake and structural engineering. The author is now familiar with the terminology and methodology used in the project, from the formation of earthquake to the seismic capacity of high-rise building. The author has also learnt the use of the software, ETABS, to do the modeling of the building. This has enhanced the author's insights into the seismic safety assessment in Singapore. Singapore has no local seismicity but is affected by seismic effects resulting from the Sumatra fault and Sumatra Subduction zone. The effect of the relative distance between Singapore and epicenter, the magnitude of seismic load and the influence of soil condition are 3 influential factors that determines the impact of earthquake. The response of tall buildings is also explained in the report. In chapter 3 of the report, topics covered includes an overview of the building plan, the finite element method, damping ratio, eigenvector analysis, Ritz-vector analysis and the fast Fourier transform (FFT) analysis. In the discussion and evaluation section of the report, it will describe the dynamic characteristics of the building which includes the time period & frequency, modal participating mass ratios and the modal shapes of the 12 modes. The peak ground acceleration (PGA) is a measure of earthquake acceleration on the ground, therefore the author will carry out a time history analysis of the seismic data (Bengkulu earthquake dated 12 Sep 07) used in the project. The author used the fast Fourier transform (FFT) method to determine the predominant frequency of the building by transforming the roof acceleration time history at sensor location of model into a frequency domain graph instead of a time domain graph. The maxima of the Fourier amplitude will be the predominant frequency of the building and correlating with the modal responses. Lastly, the height of the building is plotted against the inter-storey drift ratios so as to determine the elevation of building at which the maximum drift occurred. In conclusion, the seismic recordings used in the project are weak tremors and the first 4 modes of responses are dominant enough to predict the seismic response of the building.